H. Bergstrom’s asymptotic expansions - Bikelis, Algimantas; Galinskis, Audrius (Lietuvos matematikos rinkinys, 2008)
In this work it is researched H. Bergstrom work about asymptotic behavior of convolutions of probability distributions. We give the theorem about the members of expansion in decreasing order and the remainder term estimation. There we propose apply Levy–Scheffer polynomials and to construct pseudomoments for more profound H. Bergstrom’s asymptotic expansion investigations.